Lethal combat and sex ratio evolution in a parasitoid wasp. - Innocent, T; Savage, J; West, SA; Reece, SE (2007)
Sex allocation theory provides excellent opportunities for testing how behavior and life histories are adjusted in response to environmental variation. One of the most successful areas from this respect is Hamilton's local mate competition theory. As predicted by theory, a large number of animal species have been shown to adjust their offspring sex ratios (proportion male) conditionally, laying less female-biased sex ratios as the number of females that lay eggs on a patch increases. However, recent studies have shown that this predicted pattern is not followed by 2 parasitoid species in the genus Melittobia, which always produce extremely female-biased sex ratios. A possible explanation for this is that males fight fatally and that males produced by the first female to lay eggs on a patch have a competitive advantage over later emerging males. This scenario would negate the advantage of later females producing a less female-biased sex ratio. Here we examine fatal fighting and sex ratio evolution in another species, Melittobia acasta. We show that females of this species also fail to adjust their offspring sex ratio in response to the number of females laying eggs on a patch. We then show that although earlier emerging males do have an advantage in winning fights, this advantage 1) can be reduced by an interaction with body size, with larger males more likely to win fights and 2) only holds for a brief period around the time at which the younger males emerge from their pupae. This suggests that lethal male combat cannot fully explain the lack of sex ratio shift observed in Melittobia species. We discuss alternative explanations.